AN ANALYSIS OF FIGURATIVE LANGUAGE AND IMAGERY USED IN DUA LIPA’S SONG “LEVITATING” - Atika Anggela Putri; Nur Laila Molla; Sanday Jamaludin (IKIP Siliwangi, 2022)
This research aimed to identify kinds figurative language and imagery, also to describe the contextual meaning. This research used descriptive qualitative method. The figurative language and imagery was analyzed by using Arp and Johnson’s theory in their book entitled “Perrine’s Literature Structure, Sound & Sense” 13rd edition. The subject of this research was Dua Lipa’s song lyric “Levitating.” The results of this research: there are 17 figurative languages used in this song : 1 or 6% simile, 2 or 12% metaphor, 9 or 53% overstatement, and 5 or 29% symbol. There are 22 song lyrics that contains imagery : 8 or 36% visual imagery, 1 or 5% auditory imagery, 5 or 23% organic imagery, and 8 or 36% kinesthetic imagery. From the results of the analysis, it can be concluded that figurative language and imagery have an important role in this song. Because they are able to beautify the song and help the listeners to imagine the story and characters based on the illustrations that the songwriter has provided in the song, also help them to better understand the meaning behind the lyrics of the song.